Vitamin E intake and multiple health outcomes: an umbrella review - Zhang, Tianyi; Yi, Xianyanling; Li, Jin; Zheng, Xiaonan; Xu, Hang; Liao, Dazhou; Ai, Jianzhong (Frontiers in Public Health, 2023)
Background The benefits of vitamin E (VE) for multiple health outcomes have been well evaluated in many recent studies. Objective The purpose of this umbrella review was to conduct a systematic evaluation of the possible associations between VE intake and various health outcomes. Methods We systematically searched various databases, such as PubMed, Embase, and the Web of Science, to identify related meta-analyses of observational studies and randomized trials. We estimated the effect size of each association by using the random or fixed effects models and the 95% confidence intervals. We used standard approaches to evaluate the quality of the articles (AMSTAR) and classified the evidence into different levels of quality (GRADE). Results A total of 1,974 review articles were searched, and 27 articles with 28 health outcomes were yielded according to our exclusion criteria. The intake of VE was inversely associated with the risk of breast cancer, lung cancer, esophageal cancer, gastric cancer, pancreatic cancer, kidney cancer, bladder cancer, cervical neoplasms, cardiovascular disease, Parkinson's disease, depression, age-related cataracts, metabolic syndrome, and fracture. Overall, most of the quality of the evidence was low or very low. Three outcomes (stroke, age-related cataracts, obesity) were identified as having a “moderate” level of quality. The AMSTAR scores for all health outcomes ranged from 5 to 10. Conclusion Our study revealed that VE intake is beneficially related to multiple health outcomes. However, future studies on recommended doses and recommended populations of VE are also needed. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022339571.